2021
DOI: 10.3389/fnut.2021.807574
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals the Anti-cancerous Mechanism of Licochalcone A on Human Hepatoma Cell HepG2

Abstract: Hepatocellular carcinoma is a malignancy with a low survival rate globally, and there is imperative to unearth novel natural phytochemicals as effective therapeutic strategies. Licochalcone A is a chalcone from Glycyrrhiza that displayed various pharmacological efficacy. A globally transcriptome analysis was carried out to reveal the gene expression profiling to explore Licochalcone A's function as an anti-cancer phytochemical on HepG2 cells and investigate its potential mechanisms. Altogether, 6,061 dysregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Through these effects, LA (30–70 μM) finally induces apoptosis in HepG2 cells ( Niu et al, 2018 ; Wang et al, 2018 ). LA (70 μM) can induce apoptosis of HepG2 cells by regulating the MAPK and FoxO signaling pathways ( Wang et al, 2021 ). Likewise, LB (10–120 μM) induces apoptosis in HepG2 cells by activating the extrinsic apoptotic pathway (i.e., increasing the expression of TNFR1, Fas, Fas-L, caspase-8, JUN, and Fos) and mitochondrial apoptosis pathway (i.e., increasing the expression of Bak, caspase-9, and caspase-3) ( Wang et al, 2019 ).…”
Section: Anticancer Effects Of Licochalcones On Tumor Cellsmentioning
confidence: 99%
“…Through these effects, LA (30–70 μM) finally induces apoptosis in HepG2 cells ( Niu et al, 2018 ; Wang et al, 2018 ). LA (70 μM) can induce apoptosis of HepG2 cells by regulating the MAPK and FoxO signaling pathways ( Wang et al, 2021 ). Likewise, LB (10–120 μM) induces apoptosis in HepG2 cells by activating the extrinsic apoptotic pathway (i.e., increasing the expression of TNFR1, Fas, Fas-L, caspase-8, JUN, and Fos) and mitochondrial apoptosis pathway (i.e., increasing the expression of Bak, caspase-9, and caspase-3) ( Wang et al, 2019 ).…”
Section: Anticancer Effects Of Licochalcones On Tumor Cellsmentioning
confidence: 99%
“…LA also reduced the efflux of doxorubicin and temozolomide from BCRP-mediated BCRP-MDCKII cells by downregulating the expression of breast cancer resistance protein (BCRP) ( Fan et al, 2019 ). Based on DEGs and GO and KEGG enrichment, LA showed antitumor activity against HepG2 cells, in which MAPK and FoxO signaling played essential roles ( Wang et al, 2021 ). In gefitinib-resistant non-small cell lung cancer cells (H1975), LA also reduced Hsp90 activity in gefitinib-resistant NSCLC cells (H1975) via binding to the N -terminal ATP binding site of Hsp90 to reduce drug resistance ( Seo, 2013 ).…”
Section: Anticancer Properties Of Lamentioning
confidence: 99%
“…long non-coding RNA (lncRNA) is just one of them. [5][6][7][8] Multiple studies have shown that the expression of many lncRNAs exhibits widespread interference in HCC and is deeply involved in regulating the occurrence, development, and treatment of HCC. [9][10][11] Mediating epigenetic modification, participating in the competitive endogenous RNA mechanism, and modulating the activity of transcription factors and mRNA stability are important ways for lncRNAs to affect HCC.…”
Section: Introductionmentioning
confidence: 99%